Effectiveness of Counseling on Mother's Ability in Early Detection of Young Baby Hazard Signs - Sri Sukamti; Novita Rina Antarsih (GoAcademica Research & Publishing, 2020)
Integrated Management of Young Babies (MTBM) is a method for teaching parents how to care for a child at home; Counseling parents to solve feeding problems, and advising parents about when to return to a health facility. There is no evaluation of the effective implementation of counseling on ICMI/MTBS services to the knowledge or ability of mothers to treat and detect early signs of the danger of the baby's. This study aims to determine the effectiveness of counseling in the service of MTBM on the ability of mothers to detect early signs of danger for young infants aged < 2 months. The research method uses a quasi-experimental design with one group of pre and post-test approaches. Sample of 35 babies taken in the Ciri Mekar District Health Center in Bogor in 2019. There was a significant difference in the average knowledge of mothers about basic care of young infants before and after counseling in the MTBM service p-value of 0.001, and there was a significant difference in the average ability of mothers about the detection of danger signs of young infants before and after counseling in the service of MTBM p-value 0.028. Counseling given to baby mothers less than 2 months in MTBM service is effective to improve mother's knowledge about young baby's basic care and the danger signs detection of the young.